PENGARUH CUSTOMER SATISFACTION TERHADAP BRAND LOYALTY DENGAN FINANCIAL LITERACY SEBAGAI MODERATOR (STUDI KASUS DI LLS COFFEE) - Zidane, Muhammad; sita deliyana firmialy (FEB Universitas Sam Ratulangi Manado, 2024)
Customer satisfaction is the most important thing in terms of consumer loyalty to a brand. With the financial literacy of Indonesian society still being very small, will the relationship between customer satisfaction and brand loyalty be strengthened or weakened. The research method used in this research is a quantitative research method by distributing questionnaires. The sample from this research was 101 respondents (Generation Z). The data was processed using the IBM SPSS 26 application. The results of this research are that customer satisfaction influences brand loyalty by 34.3%. financial literacy influences brand loyalty by 2.8%. However, financial literacy as a moderation is not able to moderate the influence of customer satisfaction on brand loyalty with an influence of 35.8%.